engaruh Perlakuan Uap Etanol terhadap Mutu dan Masa Simpan Bunga Kol (Brassica oleracea var. botrytis) pada Suhu Ruang - Ni Ketut Sari Martini; I Made Supartha Utama; Ida Ayu Rina Pratiwi Pudja (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
The purpose of this research was to determine the effect of ethanol vapor and to identify the best treatment concentration to maintain quality and extend the shelf life of cauliflower. The study used a completely randomized design (CRD) with five levels of ethanol concentration: 0%, 5%, 10%, 15%, and 20%. Cauliflower florets used as controls were prepared without ethanol vapor treatment and stored at room temperature. The parameters measured included respiration rate, weight loss, color, vitamin C content, total dissolved solids, organoleptic properties (color, smell, and freshness), and intensity of damage. The results showed that the 10% ethanol treatment was the best concentration, as it reduced respiration rate and weight loss, maintained color, suppressed the decrease in vitamin C content, achieved the highest organoleptic scores for color, smell, and freshness, and reduced the intensity of damage in cauliflower.